Microbiota Phenotype Promotes Anastomotic Leakage in a Model of Rats with Ischemic Colon Resection - Diego Zamorano; Dinka Ivulic; Tomeu Viver; Felipe Morales; Francisco López-Kostner; Roberto M. Vidal (Microorganisms, 2023)
Anastomotic leakage (AL) is a major cause of morbidity and mortality after colorectal surgery, but the mechanism behind this complication is still not fully understood. Despite the advances in surgical techniques and perioperative care, the complication rates have remained steady. Recently, it has been suggested that colon microbiota may be involved in the development of complications after colorectal surgery. The aim of this study was to evaluate the association of gut microbiota in the development of colorectal AL and their possible virulence strategies to better understand the phenomenon. Using 16S rRNA sequencing of samples collected on the day of surgery and the sixth day following surgery, we analyzed the changes in tissue-associated microbiota at anastomotic sites created in a model of rats with ischemic colon resection. We discovered a trend for lower microbial diversity in the AL group compared to non-leak anastomosis (NLA). There were no differences in relative abundance in the different types of microbial respiration between these groups and the high abundance of the facultative anaerobic Gemella palaticanis is a marker species that stands out as a distinctive feature.